The causal effect of gut microbiome on pulmonary artery hypertension based on a two-sample Mendelian randomization study - Detian Jiang; Yuxin Chang; Xiaowen Zhen; Xin Zhao (Nutrition & Metabolism)
Abstract Background Alterations in gut microbiota composition have been linked to the presence of pulmonary artery hypertension (PAH), but it is unclear whether gut microbiota directly causes PAH. Methods A two-sample Mendelian randomization approach was used to investigate the causal association between gut microbiota and PAH. Various MR methods were employed, including inverse variance weighted, MR-Egger, weighted median, weighted model, and simple mode, and instrumental variable heterogeneity was assessed using Cochran’s Q statistics. Results Seven bacterial genera were found to be associated with PAH in at least one MR method. Inverse variance weighted analysis showed that UBA7102 sp002315655 (odds ratio [OR] 0.36, 95% confidence interval [CI] 0.17–0.76, P = 0.007) had a protective effect against PAH. Other genera, including Anaeromassilibacillus sp001305115 (OR 1.61, 95% CI: 1.14–2.28, P = 0.006), CAG-776 sp000438195 (OR 1.40, 95% CI 1.10–1.7, P = 0.005), F0428 (OR 1.96, 95% CI 1.27–3.03, P = 0.002), GCA-900,066,495 (OR 1.66, 95% CI: 1.14–2.41, P = 0.007), Leptospirales (OR 5.81, 95% CI 1.53–22.0, P = 0.009) and Paenibacillus J (OR 3.20, 95% CI: 1.53–6.67, P = 0.001), presented a positive association with PAH. No significant instrumental variable heterogeneity was found, and but horizontal pleiotropy was not present in any bacterial taxa. Conclusions This two-sample Mendelian randomization study found that UBA7102 sp002315655, Anaeromassilibacillus sp001305115, CAG-776 sp000438195, F0428, GCA-900,066,495, Leptospirales, and Paenibacillus J may have a causal association with PAH. Further research is needed to determine the underlying mechanisms by which gut microbiota affects PAH.